Investigating the Formation Mechanism of a Nanoporous Silver Film Electrode with Enhanced Catalytic Activity for CO2 Electroreduction. Issue 21 (2nd November 2020) - Qian, Yao; Xiao, Yanjun; Qin, Tian; Zhang, Fan; Tang, Hehua; Liu, Yifan; Lin, Bo‐Lin
Abstract: Monolithic nanoporous silver (np‐Ag) fabricated by a facile electrochemical method is attractive for electrocatalytic applications. However, the conversion mechanism between Ag and AgCl remains unclear as a result of the lack of appropriate electron microscopy evidence. Herein, systematic scanning electron microscopy (SEM) of the surface and cross‐sectional views were carried out during the anodic formation and reduction of the AgCl layer. To avoid the thermal decomposition of AgCl and the destruction of the cross‐sectional morphology, Ar ion polishing at −140 °C under the cooling of liquid N2 was adopted. Our data show that the reduction process of the AgCl layer includes three processes: trigger, expansion, and shrinkage. A funnel‐like transient state was observed for the first time, leading to a new formation mechanism for the resultant np‐Ag. Outstanding performance in electrocatalytic reduction of CO2 to CO was observed for one of the nanoporous Ag films presumably due to its unique nanostructure to promote initial electron transfer and active‐site exposure. The selectivity of CO between −0.31 and −0.56 V was higher than 90 %, and reached a maximum of 96 % at −0.36 V. Abstract : Three‐step process : The growth/reduction processes of an AgCl layer to form nanoporous Ag electrodes was investigated through improved electron‐microscopic analyses. One of the nanoporous Ag films showed outstanding performance in the electrocatalytic reduction of CO2 to CO, presumably due to its unique nanostructure.